Analyzing Environmental Influences on New Structure of Solar Still Productivity: An Experimental Study in Basrah Iraq - Murtadha, Hawraa M.; Ateeq, Adnan A.; Jabbar, Tahseen A. (Basrah Journal for Engineering Sciences, 2024)
Solar desalination uses solar radiation to convert saline or seawater into clean water and is increasingly crucial due to growing pollution from industrial and automotive sources. Although solar stills offer a sustainable solution, they face challenges in terms of production efficiency. This study presents a new structural design for solar stills, which incorporates advanced insulation materials, a well-designed distillate channel, and an inclined base to enhance productivity. The research explores how different climatic conditions such as wind speed, solar radiation, and atmospheric humidity affect solar still performance. Seven experimental setups were evaluated, comparing traditional inclined stills with advanced closed-loop systems. The results demonstrated that closed-loop systems improved productivity by 28.6% compared to open-loop systems. Additionally, moderate wind speeds increased productivity by 20.82%, while partial cloud cover and light rain decreased productivity by 52.15% and 12.9%, respectively. However, light rain also enhanced condensation efficiency by cooling the glass surface. This study highlights the importance of incorporating environmental factors into the design and optimization of solar still systems for improved performance.